Endotracheal inflammatory myofibroblastic tumour: A rare cause of central airway occlusion in adults - Albert Iruthiaraj Lourdesamy Anthony; Taranjit Kaur Satnam Singh; Khai Lip Ng; Jamalul Azizi Abdul Rahaman (Respirology Case Reports, 2022)
Abstract Inflammatory myofibroblastic tumour (IMT) is an unusual myofibroblastic spindle cell neoplasm that is rarely discovered in the airway of adults. Previously, it was regarded as a reactive lesion and was infamously known as inflammatory pseudotumour before recent insights revealed that significant majority of cases harboured neoplastic genes. Diagnosis is difficult as clinical presentation and imaging findings are non‐specific. Diagnosis and a favourable prognosis require the complete resection of the tumour. Detection of the anaplastic lymphoma kinase expression via immunohistochemistry expedites diagnosis. We report a young adult with an endotracheal mass occluding the central airway. The patient successfully underwent bronchoscopic resection using interventional techniques. IMT was diagnosed. No recurrence was seen after a year of surveillance. Due to the rarity of the disease, the recurrence rates for large airway disease is unknown. Recurrence rates for pulmonary lesions is reported to be lower compared to extrapulmonary IMTs and recurrence is unlikely if compete surgical excision is achieved.